Pengantar ilmu Tasawuf - INDONESIA... (Proyek Binpertais, 1982)
ir,c.1-7/wk, c.8/ir,c.9/wk, c.10/wk, c.11-12/ast c.13/ast c.14/ir,c.15/ir,c.16/ir,c.17/ast c.18/ir,c.19/oen, c.20/tr, c.21-23/ir,c.24-27/rt.28/ws.c.29